Diseases of the Abdomen and Pelvis 2023-2026 Diagnostic Imaging - Hodler, Juerg; Kubik-Huch, Rahel A.; Roos, Justus E.; von Schulthess, Gustav K. (IDKD Springer Series, 2023)
This open access book deals with imaging of the abdomen and pelvis, an area that has seen considerable advances over the past several years, driven by clinical as well as technological developments. The respective chapters, written by internationally respected experts in their fields, focus on imaging diagnosis and interventional therapies in abdominal and pelvic disease; they cover all relevant imaging modalities, including magnetic resonance imaging, computed tomography, ultrasound, and positron emission tomography. As such, the book offers a comprehensive review of the state of the art in imaging of the abdomen and pelvis. IDKD books are extensively re-written every four years. As a result, they offer a comprehensive review of the state of the art in imaging. The book is clearly structured with learning objectives, abstracts, subheadings, tables and take-home points, supported by design elements to help readers easily navigate through the text. As an IDKD book, it is particularly valuable for general radiologists, radiology residents, and interventional radiologists who want to update their diagnostic knowledge, and for clinicians interested in imaging as it relates to their speciality.